PENGARUH JENIS WADAH DAN LAMA FERMENTASI TERHADAP KUALITAS DADIH SEBAGAI RANCANGAN LEMBAR KERJA SISWA ( LKS ) BIOTEKNOLOGI KONVENSIONAL KELAS XII SISWA SMA - Pertiwi, Yohana; Mahadi, Imam; Darmawati, Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Curd is a fermented dairy product which is quite popular in West Sumatra and Riau region. The purpose of this research is to know the influence of bamboo container type, glass container, plastic container and fermentation length to the quality of curd. This Research Using Completely Randomized Design (RAL) with factorial pattern of 4X3 with 3X replicates. The intended treatment is foktor A The type of container used is bamboo container, glass container and plastic container. While factor B is fermentation length that is 48,72,96 and 120 hours. The parameters observed through the test of protein, fat, pH and organoleptic test on 10 panelists included flavor, aroma, texture color and preferences showed that bamboo containers with 48 hours and 72 hours fermentation had better quality compared to glass containers and Plastic. The longer the fermentation, the protein, fat and pH of the curd decreased both in bamboo containers, glass containers and plastic containers. The results of this study can be used as a design of learning resources in the form of student worksheets in the conventional biotechnology concept of grade XII high school students.Keywords: Length of Fermentation, Type of Container, Quality, Milk Curd